EFFECT OF HABITAT DEGRADATION ON BREEDING WATER BIRDS AT KALLAR KAHAR LAKE DISTRICT CHAKWAL - M. Rais; B. Kabeer; M. Anwar; T. Mehmood (Journal of Animal and Plant Sciences, 2010)
Degradation in the wetland ecosystem can change water bird species composition, particularly breeding fauna, by influencing habitat use for nesting and breeding activities. Kallar Kahar Lake is on the brink of drying. Eastern marshy area of the lake which had served as a perfect retreat for Egretta garzetta (little egret), Ardea cinerea (grey heron), Ardea purpurea (purple heron), Gallinula chloropus (common moorhen) and Porphyrio porphyrio (purple moorhen) has now been completely dried. It has been heavily infested with dried Phragmites sp. offering roosting sites to Corvus splendens (house crows) and Acridotheres tristis (common myna).Reduced freshwater supplies into the lake, excessive growth of reeds and land encroachment are responsible for the current degraded state of the lake. Thereeds cover had an estimated 25 and 13 nests per hectare of Nycticorax nycticorax (black-crowned night heron) and Egretta garzetta (little egret) respectively during April-May, 2009. Some wading birds such as Himantopus himantopus (black-winged stilt) were found breeding in the vegetation in the 2010.
Keywords: Degradation; ecosystem; habitat; breeding fauna